Budget Hotel Strategy In Increasing Occupancy (Hotel Pantai Paris Tigaras District. Simalungun) - Mulyadi, Bejo; Riady, Iwan; Rosari, Dina; Gunawan, Bakti (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
This study concern to examine how to implement strategies to increase the occupancy of Budget Hotels around Pantai Paris, Simalungun Regency. The method used in this study was purposive sampling taken intentionally. The analysis tool used is SWOT Analysis which consists of IE Matrices, IFAS/EFAS, and SWOT/TOWS Matrices. From this research, it is known that the Pantai Paris Budget Hotel Simalungun Regency is currently in quadrant I IFAS 1,665 EFAS 1,020, the strategy that needs to be done is the S – O (Strength – Opportunity) strategy, which is a strategy that takes advantage of the opportunities / strengths owned by the Budget Hotel. Alternative strategies are: Maintaining good relations with the local community, Brand positioning as a good hotel, Increasing cooperation with cuttings holders, Providing excellent service to guests, Analyzing room quality and prices for similar hotels, Utilizing technological advances, Rearrangement of every hotel facility from rooms to public facilities, Making training to employees (appearance, service), Rearranging every hotel facility from rooms to public facilities in the hotel needs to be done to maintain the quality of the hotel, Making training that refers to technological developments.